The Impact of the New Normal Era on Investor Trading Behavior: Evidence from the IDX Capital Market School, Central Kalimantan Province, Indonesia - Wardani, Ocmi Nidia; Meina Wulansari Yusniar (Open Access Indonesia Journal of Social Sciences, 2024)
The COVID-19 pandemic and the subsequent "new normal" era have significantly impacted financial markets worldwide. This study investigates how investor perceptions, namely return expectations, risk tolerance, and risk perception, influence trading behavior in the Indonesian Stock Exchange (IDX) during this period. A quantitative approach was employed, utilizing a questionnaire to collect data from 50 active investors registered with the IDX Capital Market School in Central Kalimantan Province. Structural Equation Modeling (SEM) with SmartPLS 3.0 was used to analyze the data. The findings reveal that return expectations positively and significantly influence trading behavior. However, risk tolerance and risk perception were found to have no significant effect on trading behavior during the new normal era. These results suggest that investors in the IDX prioritize return expectations over risk considerations in the new normal era. This highlights the need for investor education and policy interventions to promote a more balanced approach to investment decision-making.